The Role of Financial Technology In The Development of The Islamic Financial Industry In Europe: Qardus Platform As A Model - Alzobui, Heyam Sami; Al-Zaghul, Mohammed Husain (Ta'amul: Journal of Islamic Economics, 2024)
The study aimed to demonstrate the role of Islamic financial technology platforms that they can contribute to the development of the Islamic financial industry and its spread in the countries of the world, in line with the technological development and digital transformation that the world is witnessing, which includes most sectors, and the steps taken by Islamic financial institutions to keep pace with the development taking place in the world. In order to preserve the existence of Islamic finance and accelerate the growth of the Islamic economy, among these platforms that deal in accordance with the provisions of Islamic Sharia that have emerged in Europe is the Qardus platform, in which financing is characterized by high risk and high reward. The study concluded that Islamic financial technology platforms have a major role in The development of the Islamic financial industry globally